2018
DOI: 10.3389/fmicb.2018.01463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Virulence Profiles of Colistin-Resistant Klebsiella pneumoniae Blood Isolates From the Hospital Agency “Ospedale dei Colli,” Naples, Italy

Abstract: Resistance to colistin is increasingly reported in Klebsiella pneumoniae clinical isolates. The aim of this study was to analyze the molecular epidemiology and virulence profiles of 25 colistin-resistant K. pneumoniae blood isolates from the Hospital Agency “Ospedale dei Colli,” Naples, Italy, during 2015 and 2016. Colistin MIC values of isolates ranged from 4 to 256 mg/L. The inactivation of the mgrB gene, encoding a negative regulator of the PhoQ/PhoP signaling system, was the most frequent mechanism of coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 47 publications
14
40
0
Order By: Relevance
“…The emergence of other KPC-3-producing high-risk K. pneumoniae clones with recognized worldwide expansion (ST392, ST307) and additional enhanced virulence and/or antibiotic resistance (ST307, ST22) is of concern. The ST392 clone has been recently reported in other countries (China, Italy, Mexico) [ 13 , 14 , 15 ] but to our knowledge this is the first study to describe KPC-3-producing K. pneumoniae ST392 isolates in Portugal. Although detected in small numbers, the identification of 4 ST307 isolates producing KPC-3 among medical and surgical units is of great concern because of its higher resistance profile and the recognized virulence potential (high resistance to complement-mediated killing) of this high-risk clone reported worldwide [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 90%
“…The emergence of other KPC-3-producing high-risk K. pneumoniae clones with recognized worldwide expansion (ST392, ST307) and additional enhanced virulence and/or antibiotic resistance (ST307, ST22) is of concern. The ST392 clone has been recently reported in other countries (China, Italy, Mexico) [ 13 , 14 , 15 ] but to our knowledge this is the first study to describe KPC-3-producing K. pneumoniae ST392 isolates in Portugal. Although detected in small numbers, the identification of 4 ST307 isolates producing KPC-3 among medical and surgical units is of great concern because of its higher resistance profile and the recognized virulence potential (high resistance to complement-mediated killing) of this high-risk clone reported worldwide [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 90%
“…These strains belonged to different STs and carried loss-of-function mutations in mgrB , encoding a repressor of the arn operon responsible for lipid A aminoarabinosylation. 39 BBN149 at 30 μM strongly reduced the colistin MIC for all the colistin-resistant K. pneumoniae strains, while it did not increase colistin activity against the colistin-susceptible KP-Mo-26 and KP-Mo-27 isolates (Table 1 ), implying that the inhibitory activity of this compound on colistin resistance is not restricted to P. aeruginosa. Time–kill and growth assays confirmed that in K. pneumoniae the BBN149/colistin combination is also bactericidal at 2× MIC of colistin (Figure S5 ) and that BBN149 has no inhibitory effect in the absence of colistin (Figure S4 ).…”
Section: Resultsmentioning
confidence: 97%
“…However, in a genomic survey of 164 PR clinical isolates, we recently observed that 40% harbored wild-type (WT) mgrB . In addition, we identified more than 80 mutations, the majority of which were within three two-component systems— phoP/Q , crrA/B , and pmrA/B ( Macesic et al, 2020 )—which have been proposed as alternative pathways to PR ( Leung et al, 2017 ; Esposito et al, 2018 ). In combination with mgrB , we will refer to these genes as the “canonical genes.” These findings highlight the heterogeneous nature of PR and the urgent need for functional validation of the observed alleles ( Macesic et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%